AI ADOPTION IN THE DIGITAL CREATIVE INDUSTRY: WHY TALENT READINESS OVERWEIGHS ORGANIZATIONAL SUPPORT? - Akbar, Maulana; Sihite, Mombang; Nawasiah, Nana (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
The rapid development of artificial intelligence (AI) is fundamentally reshaping the landscape of digital transformation in various sectors. This phenomenon is particularly critical in the digital creative industry and application development startups, which rely heavily on technological innovation while operating in dynamic and highly competitive business environments. However, despite the promised operational benefits, the AI adoption rate among workers still shows significant variation. This study aims to empirically analyze the key determinants of AI adoption among workers in Jakarta's digital creative sector by focusing on the role of talent capabilities, talent management strategies, IT infrastructure, and organizational support. This study uses a quantitative approach through a structured survey of 226 workers in digital startups located in Jakarta and is analyzed using binary logistic regression to test the predictive variables. The statistical results showed that talent capabilities had a positive and significant effect on AI adoption, proving that individual technical competence is the primary driver of usage behavior. Conversely, talent management strategies, IT infrastructure, and organizational support did not show a statistically significant influence. These findings indicate that AI adoption in the creative economy context is driven more by individual readiness than by top-down managerial or structural factors. Consequently, entrepreneurs in the creative industry should prioritize strengthening individual talent capabilities through targeted upskilling and continuous learning programs as the main foundation for driving effective digital transformation and ensuring business sustainability.